2021
DOI: 10.1177/21650799211012675
|View full text |Cite
|
Sign up to set email alerts
|

Survivors’ Dilemma: Young Adult Cancer Survivors’ Perspectives of Work-Related Goals

Abstract: Background: Young adult cancer survivors have significant work-related challenges, including interruptions to education and employment milestones, which may affect work-related goals (WRGs). The study purpose was to explore posttreatment perspectives of WRGs in a sample of young adult hematologic cancer survivors. Methods: This qualitative descriptive study used social media to recruit eligible cancer survivors (young adults working or in school at the time of cancer diagnosis). Data were collected through tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 58 publications
1
15
0
1
Order By: Relevance
“…The study was approved by the New York University Institutional Review Board (2020-4281). Eligibility, recruitment, and data collection methods of the parent study are described in detail elsewhere (Ghazal, Merriman, et al, 2021). Briefly, participants included YA leukemia and lymphoma survivors who had completed active treatment within 5 years of diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was approved by the New York University Institutional Review Board (2020-4281). Eligibility, recruitment, and data collection methods of the parent study are described in detail elsewhere (Ghazal, Merriman, et al, 2021). Briefly, participants included YA leukemia and lymphoma survivors who had completed active treatment within 5 years of diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding perceptions of work and describing work-related outcomes among the cancer survivorship continuum is critical; work is one of the greatest issues affecting quality of life (QOL) among cancer survivors (Peteet, 2000). We previously reported that hematologic YACS experienced “survivors’ dilemma” when reflecting on their work-related goals (Ghazal, Merriman, et al, 2021). Survivors continuously balanced factors related to changed self-identity, perceived work ability, and new or worse worry about money and difficulty paying for basics, which affected their QOL.…”
mentioning
confidence: 99%
“…Monitoring and understanding the long-term consequences that CCS can develop through their life is relevant for public health [ 1 ]. Besides the possible onset of physical late effects induced by cancer treatments, CCS are at risk of developing psychological and socioeconomic vulnerability [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Key developmental tasks such as educational achievements, employment, financial independence, and job satisfaction are crucial factors for a good quality of life (QoL), for CCS as well as for their healthy peers [ 4 , 6 , 7 ]. However, due to their previous cancer, CCS may have greater difficulty coping with challenges that entering adulthood implies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation